101 Dalmatians - Peet, Bill.; Smith, Dodie, 1896-; Walt Disney Home Video (Firm) ([United States] : Walt Disney Home Video ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 1998)
Dalmatians Pongo and Perdita settle into their owners' flat in London to become proud parents of 15 precocious pups. It's one big happy dog family until the evil Cruella De Vil kidnaps the puppies, along with every other Dalmatian in the city. It's up to Pongo and Perdita to unite the entire animal population in a mission to help the courageous pups outsmart their captor.
Title from cassette label.
At head of title: Disney's masterpiece.
"Walt Disney masterpiece."
Videocassette release of the 1961 motion picture.
Based on the book: The hundred and one dalmatians / by Dodie Smith.
"Special bonus: exclusive MouseWorks featurette starring Pluto!"--Container.
Keywords: Dogs -- Juvenile fiction; Feature films; Animated films; Children's films; Video recordings for the hearing impaired